2001
DOI: 10.1176/appi.ps.52.5.660
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Religious Coping Among Persons With Persistent Mental Illness

Abstract: The results of the study suggest that religious activities and beliefs may be particularly compelling for persons who are experiencing more severe symptoms, and increased religious activity may be associated with reduced symptoms. Religion may serve as a pervasive and potentially effective method of coping for persons with mental illness, thus warranting its integration into psychiatric and psychological practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
164
1
15

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(196 citation statements)
references
References 9 publications
12
164
1
15
Order By: Relevance
“…Negative religious coping includes passive waiting for God to control the situation, redefining the stressor as a punishment from God or as an act of the devil and, questioning God's love. 24,[85][86] 3. Religious practices Public and private religious practices can help to maintain mental health and prevent mental diseases.…”
Section: -84mentioning
confidence: 99%
“…Negative religious coping includes passive waiting for God to control the situation, redefining the stressor as a punishment from God or as an act of the devil and, questioning God's love. 24,[85][86] 3. Religious practices Public and private religious practices can help to maintain mental health and prevent mental diseases.…”
Section: -84mentioning
confidence: 99%
“…46 Spirituality and religion are often critical to recovery among individuals with SMI 47,48 and may contribute significantly to individuals_ well-being 48 by providing hope, comfort, love, and acceptance, 49,50 and a sense of control and meaning. 51 Religious/spiritual activities may have positive effects 51,52 by providing role models for behavior, contact with other individuals, and material assistance, 49,53 and may be especially important for those with heightened levels of stress and debilitation. 51 HIV prevention research efforts have not adequately examined the role of religious/spiritual beliefs in reducing HIV risk among either Hispanics or SMI persons.…”
mentioning
confidence: 99%
“…51 Religious/spiritual activities may have positive effects 51,52 by providing role models for behavior, contact with other individuals, and material assistance, 49,53 and may be especially important for those with heightened levels of stress and debilitation. 51 HIV prevention research efforts have not adequately examined the role of religious/spiritual beliefs in reducing HIV risk among either Hispanics or SMI persons. Our study examined contextual factors relevant to HIV risk among a sample of Puerto Rican and Mexican women diagnosed with SMI.…”
mentioning
confidence: 99%
“…Trepper et al [7] found that participants experiencing greater symptom severity and lower overall functioning are more likely to use religious activities as part of their coping. Symptom-related stress leads to greater use of religious coping, a phenomenon that has also been shown in other studies [8,9].…”
Section: Open Accessmentioning
confidence: 99%
“…Furthermore, emotional struggles and feelings of rejection can be reinforced by religious communities who see mental disorders as signs of moral or spiritual weakness or failure. Prayer or other religious rituals can become compulsive and interfere with overall daily functioning [7]. Finally, beliefs involving themes of divine abandonment or condemnation, unrelenting rejection, or powerful retribution may make recovery seem unattainable or unimportant [37].…”
Section: The Extended Bio-psycho-social Modelmentioning
confidence: 99%